T cells display mitochondria hyperpolarization in human type 1 diabetes - Chen, Jing; Chernatynskaya, Anna V.; Li, Jian-Wei; Kimbrell, Matthew R.; Cassidy, Richard J.; Perry, Daniel J.; Muir, Andrew B.; Atkinson, Mark A.; Brusko, Todd M.; Mathews, Clayton E. (Scientific reports, 2017)
T lymphocytes constitute a major effector cell population in autoimmune type 1 diabetes. Despite essential functions of mitochondria in regulating activation, proliferation, and apoptosis of T cells, little is known regarding T cell metabolism in the progression of human type 1 diabetes. In this study, we report, using two independent cohorts, that T cells from patients with type 1 diabetes exhibited mitochondrial inner-membrane hyperpolarization (MHP). Increased MHP was a general phenotype observed in T cell subsets irrespective of prior antigen exposure, and was not correlated with HbA1C levels, subject age, or duration of diabetes. Elevated T cell MHP was not detected in subjects with type 2 diabetes. T cell MHP was associated with increased activation-induced IFNγ production, and activation-induced IFNγ was linked to mitochondria-specific ROS production. T cells from subjects with type 1 diabetes also exhibited lower intracellular ATP levels. In conclusion, intrinsic mitochondrial dysfunction observed in type 1 diabetes alters mitochondrial ATP and IFNγ production; the latter is correlated with ROS generation. These changes impact T cell bioenergetics and function.